Syzygium aqueum: A Polyphenol- Rich Leaf Extract Exhibits Antioxidant, Hepatoprotective, Pain-Killing and Anti-inflammatory Activities in Animal Models - Mansour Sobeh; Mona F. Mahmoud; Ganna Petruk; Samar Rezq; Mohamed L. Ashour; Fadia S. Youssef; Assem M. El-Shazly; Daria M. Monti; Ashraf B. Abdel-Naim; Michael Wink (Frontiers Media S.A., 2018)
Syzygium aqueum is widely used in folk medicine. A polyphenol-rich extract from its leaves demonstrated a plethora of substantial pharmacological properties. The extract showed solid antioxidant properties in vitro and protected human keratinocytes (HaCaT cells) against UVA damage. The extract also reduced the elevated levels of ALT, AST, total bilirubin (TB), total cholesterol (TC) and triglycerides (TG) in rats with acute CCl4 intoxication. In addition to reducing the high MDA level, the extract noticeably restored GSH and SOD to the normal control levels in liver tissue homogenates and counteracted the deleterious histopathologic changes in liver after CCl4 injection. Additionally, the extract exhibited promising anti-inflammatory activities in vitro where it inhibited LOX, COX-1, and COX-2 with a higher COX-2 selectivity than that of indomethacin and diclofenac and reduced the extent of lysis of erythrocytes upon incubation with hypotonic buffer solution. S. aqueum extract also markedly reduced leukocyte numbers with similar activities to diclofenac in rats challenged with carrageenan. Additionally, administration of the extract abolished writhes induced by acetic acid in mice and prolonged the response latency in hot plate test. Meanwhile, the identified polyphenolics from the extract showed a certain affinity for the active pockets of 5-lipoxygenase (5-LOX), cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) explaining the observed anti-inflammatory activities. Finally, 87 secondary metabolites (mostly phenolics) were tentatively identified in the extract based on LC-MS/MS analyses. Syzygium aqueum displays good protection against oxidative stress, free radicals, and could be a good candidate for treating oxidative stress related diseases.